Reconstruction of the Concept of Nushuz of the Wife in the Digital Era - Rokan, Mustafa Kamal; Yazid, Imam; Makky, Ahmad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
The increasing number of divorces has been largely affected by technological developments, including social media, which are used in a way that may lead wives to commit nushuz behavior. This present study aimed at reconstructing the nushuz of the wife in the digital era, a concept commonly known as the wife leaving her house without the permission of the husband. As a normative study, the study applied the conceptual approach. The study collected data by using the documentation study or library research, and analyzed the data by reading, examining, linking, and interpreting the data, and then elaborated the data descriptively. The findings revealed that social media has been used as a platform to publicly show the women’s beauty, reveal their aurat (intimate parts), spread gossips, share infidelity behavior, and many others which violate the religious norms and the universal, collective, individual, local and traditional values as well. Ideally, all of these should be kept private at home, as the home itself is the place to protect anything within it. The elimination of politeness boundaries and rules of interaction between men and women as a consequence of activities on social media has made nushuz of the wife irrelevant to be interpreted simply as the wife leaving the house without the permission of the husband. The meaning of house in the physical sense and that of social media should be equal in the context of the household. Nushuz should be interpreted in a broader perspective following the increasing development of modern technologies.